Factors Affecting Regional Fiscal Capacity In Ambon City - Sherly Ferdinandus; Dientje Rumerung; Muhammad Bugis; Mohamad. R. Serang; Amin (LP2M IAIN Palopo, 2025)
This study aims to analyze the factors that influence Regional Fiscal Capacity (KFD) in Ambon City. The study used secondary time series data for 10 years (2014–2023) in Ambon City. The analysis method used was Multiple Linear Regression with the dependent variable (Y) being the Fiscal Capacity Index, and the independent variables being Regional Original Income (PAD) (X1), Economic Growth Rate (X2), and Population (X3). Key Results: The results of the regression analysis showed that the independent variables PAD (X1), Economic Growth Rate (X2), and Population (X3) did not have a significant effect on the Regional Fiscal Capacity of Ambon City. Implications/ConsequencesAruan:TeamThis study provides an empirical contribution because it differs from general assumptions and previous research (state of the art), which often shows a positive relationship. These results highlight a unique problem or phenomenon in Ambon City, where the theoretically common factors driving fiscal capacity (PAD, economic growth, population) are not working effectively.